Creating a Culture of Active Offer in Both Official Languages: A Case Study of a Dialogue - Forgues, Éric; Paulin, Christine (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles.